Mimicry of surgical site infection – Case report. (2020) - Bretschneider, H.; Helbig, S.; Kleber, C.; de With, K.; Stiehler, M.
Highlights: Calciphylaxis may cause severe soft tissue complications after total joint arthroplasty. Caliphylaxis is a potential differential diagnosis to surgical site infection in patients with chronic kidney disease. Skin biopsy should be taken in case of suspected calciphylaxis to confirm the diagnosis. Abstract: Background context: Calciphylaxis is a rare complication of secondary hyperparathyroidism caused by calcifications of small blood vessels in the skin and soft tissue. The disease occurs almost exclusively in patients with chronic kidney disease and has an incidence of approximately 50 cases per year in Germany [1 ]. Purpose: We present a case of a 61-year-old woman with calciphylaxis in connection with a primary knee endoprosthesis implantation. Study design: Case report. Methods: A review of the medical records since the time of initial hospital admission throughout the entire hospitalization until the death of the patient was performed. Results: Calciphylaxis caused severe soft tissue complications after total joint arthroplasty. Despite interdisciplinary therapy, including revision and plastic surgery as well as intensive care, the patient died 4 months after primary total knee arthroplasty due to septic multi-organ failure. Conclusion: Calciphylaxis may cause severe soft tissue complications after total joint arthroplasty and should be considered as potential differential diagnosis to surgical site infection. This is the first case report on calciphylaxis as direct complication of total joint replacement surgery.